2020
DOI: 10.31234/osf.io/vpc39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are the more flexible great-tailed grackles also better at behavioral inhibition?

Abstract: Behavioral flexibility should theoretically be positively related to behavioral inhibition (hereafter referred to as inhibition) because one should need to inhibit a previously learned behavior to change their behavior when the task changes (the flexibility component;). However, several investigations show no or mixed support of this hypothesis, which challenges the assumption that inhibition is involved in making flexible decisions. We aimed to test the hypothesis that behavioral flexibility (measured as reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(51 reference statements)
0
12
0
1
Order By: Relevance
“…For example, it is possible that performance on serial reversal learning and solution switching on the MAB tasks is reflective of a trait other than behavioral flexibility, like inhibition (MacLean et al, 2014). Indeed, we previously found that the more flexible grackles on the serial reversal learning task were also better able to inhibit responding to a non-rewarded stimulus in a go/no-go task thought to measure self-control (Logan et al, 2021). Consequently, more research is needed to interpret whether some aspect of performance on the go/no-go task reflects behavioral flexibility or whether performance on the reversal learning task is influenced by inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that performance on serial reversal learning and solution switching on the MAB tasks is reflective of a trait other than behavioral flexibility, like inhibition (MacLean et al, 2014). Indeed, we previously found that the more flexible grackles on the serial reversal learning task were also better able to inhibit responding to a non-rewarded stimulus in a go/no-go task thought to measure self-control (Logan et al, 2021). Consequently, more research is needed to interpret whether some aspect of performance on the go/no-go task reflects behavioral flexibility or whether performance on the reversal learning task is influenced by inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The 12 adult grackles (Fajita, Mole, Tomatillo, Habanero, Chalupa, Tapa, Adobo, Diablo, Burrito, Marisco, Queso, and Yuca) and 2 juvenile grackles (Taco and Chilaquile; see Table 1 ) that underwent touchscreen training were caught in the wild in Tempe, Arizona, USA, from September 2018 through November 2019 and temporarily brought into outdoor aviaries for behavioral testing before being released back to the wild. Each bird was measured, then color-marked with leg bands in unique combinations for identification, and blood samples were drawn prior to being placed in the aviary as part of other research (see [ 22 24 ]). Grackles were individually housed in an aviary (each 2.44 m long by 1.22 m wide by 2.13 m tall) at Arizona State University for a maximum of six months.…”
Section: Methodsmentioning
confidence: 99%
“…Before beginning TOC training to prepare the birds for the TOC experiments (go/no go: see [ 24 ] for details; causal cognition: see [ 22 ]; reversal learning: see [ 23 ] these individuals experienced non-TOC experiments). Non-TOC experiments included a color tube reversal learning experiment and a puzzle box experiment (see [ 23 ] for details), a detour experiment (see [ 24 ]), exploration and boldness assays (see [ 33 ]), and demonstrator training for a social learning experiment ([see 34 ]) and see Table 1 for a complete summary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data was used to estimate the scaled mass index (SMI), which has become the primary method for quantifying energetic conditions within and among bird populations [43][44][45]. Then, grackles were either immediately released or temporarily brought into aviaries for behavioral testing (as part of other investigations [46][47][48][49]) and then released back to the wild. A second blood sample was collected and processed as described above from those grackles kept in the aviaries to confirm the haemosporidian diagnostic before being released.…”
Section: Study Area and Samplesmentioning
confidence: 99%